2022
DOI: 10.1097/aco.0000000000001098
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and the microcirculation: the impact on outcomes

Abstract: Purpose of reviewAdvances in the treatment of septic shock have historically focused on resuscitation endpoints, mainly mean arterial pressure and cardiac output. As the definitions of sepsis and septic shock have shifted to focus on the diversity of causes of dysregulated host-response we have seen an emerging phenotype where tissue hypoxia persists despite adequate macrocirculatory parameters. Interest in the topic of microcirculation is re-emerging as validated bedside techniques for hemodynamic monitoring,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Other variables were significantly different between the SAE and non-SAE groups, including lactate levels. Elevated serum lactate levels indicate an oxygen supply/demand mismatch and microcirculatory impairment, inducing tissue ischemia and hypoxia in sepsis [ 40 ]. Previous studies have suggested that lactate is an important indicator for predicting the prognosis of patients with sepsis and is often used to evaluate disease severity and guide treatment [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other variables were significantly different between the SAE and non-SAE groups, including lactate levels. Elevated serum lactate levels indicate an oxygen supply/demand mismatch and microcirculatory impairment, inducing tissue ischemia and hypoxia in sepsis [ 40 ]. Previous studies have suggested that lactate is an important indicator for predicting the prognosis of patients with sepsis and is often used to evaluate disease severity and guide treatment [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Direct visualization techniques are therefore usually limited to sedated patients [28]. The other major problem is that specific microcirculatory goals are not yet well defined [29,30 ▪▪ ,31 ▪ –33 ▪ ,34].…”
Section: Microcirculationmentioning
confidence: 99%
“…For the earliest possible diagnosis of developing sepsis, which is considered a prerequisite for targeted therapeutic intervention, a combination of clinical observations and findings with various biomarkers has been recommended [ 21 ]. The path from infection, which at the beginning, in many cases, is not clearly identifiable, to sepsis is via organ dysfunction, which can occur at various sites and is the result of microcirculatory disturbances, most of which can be assessed and monitored including the hematologic system [ 22 , 23 ]. Preclinical studies have shown that in the so-called thrombo-inflammation of sepsis, among others, microcirculatory dysfunction is an early phenomenon [ 24 ], in which the endothelial glycocalyx plays a key role [ 25 ].…”
Section: Diagnosis and Management Of Sepsis-induced Coagulopathymentioning
confidence: 99%